1988
DOI: 10.1002/crat.2170230419
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrochemical solar cells based on TiS2/TiO2(TiOxSy) photoelectrodes

Abstract: A new photoelectrode of TiS,/TiO, alloy with a possible new TiO,S,. phase has been synthesized for the first time in the present investigation. This photoanode exhibits improved photoelectrochemical (PEC) response as compared to either TiS, or TiO, photoelectrode. With this new photoelectrode high PEC conversion efficiency is evidenced by large photovoltage (840 mv) and significantly high photocurrent density (40 mA/cm2). The photovoltage obtained in the present system is significantly high and the photocurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Recently, there has been increasing interest in the development of oxygen sensors based on the change in the luminescent or electrical properties of materials caused by their interaction with oxygen. It has been reported that the partial desulfurization of titanium sulfide resulted in an increase of the photocurrent 26. The single‐layered titanium sulfide in this report has a 2D shape that could be incorporated into devices and the change in its optical properties and possible changes in its electrical properties brought about by the structural change from titanium sulfide to titanium oxide could be applied to the development of new oxygen sensors 27…”
Section: Synthesis Of Titanium Sulfide Nanodisks[a]mentioning
confidence: 76%
“…Recently, there has been increasing interest in the development of oxygen sensors based on the change in the luminescent or electrical properties of materials caused by their interaction with oxygen. It has been reported that the partial desulfurization of titanium sulfide resulted in an increase of the photocurrent 26. The single‐layered titanium sulfide in this report has a 2D shape that could be incorporated into devices and the change in its optical properties and possible changes in its electrical properties brought about by the structural change from titanium sulfide to titanium oxide could be applied to the development of new oxygen sensors 27…”
Section: Synthesis Of Titanium Sulfide Nanodisks[a]mentioning
confidence: 76%
“…Chandra Babu and Srivasta appear to be the first researchers to report experiments aimed specifically at raising the energy of the valence band in TiO 2 . In 1988 they oxidized single crystal TiS 2 to give S-doped TiO 2 and reported photocurrents eight times higher than obtained for undoped TiO 2 .…”
Section: Introductionmentioning
confidence: 99%